Implementasi Nilai Al-Qur’an Terhadap Etos Kerja di IAIN Kendari (Studi Living Qur’an pada QS. At-Taubah Ayat 105) - Desriliwa Ade Mela; Zul Ikrom Zilsafil (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
In an institution or organization, there are goals that must be achieved. The work ethic is one of the foundations that improves the quality and performance of teaching staff who play an important role on the IAIN Kendari campus. The purpose of this study was to describe the work ethic of the lecturers at IAIN Kendari based on the verses of the Qur'an, how the work ethic of the Arabic language lecturer in Kendari is and what factors influence the work ethic of the Arabic language lecturer at IAIN Kendari. This study adopted a descriptive qualitative research method. The data collection technique is carried out by merging and analyzing inductive data. In this study the data collection method used was first observation, namely data collection techniques by making direct observations of the work activities of IAIN Kendari lecturers. So it can be concluded that the lecturer has implemented a work ethic. The Arabic language lecturers at IAIN Kendari apply a work ethic that includes sincerity, honesty, consistency, discipline and responsibility. And also the lecturers consider that work is a form of worship. Because in carrying out their duties honestly, consistently, disciplined with time and in accordance with the procedures previously set by the campus. Then there are several factors that influence the work ethic such as religious, cultural, social, economic, educational and environmental factors.